CcpA is important for growth and virulence of Enterococcus faecium - Somarajan, Sudha R; Roh, Jung H; Singh, Kavindra V; Weinstock, George M; Murray, Barbara E (Infection and immunity, 2014)
The collagen adhesin Acm was the first virulence determinant reported to be important for the pathogenesis of Enterococcus faecium in a rat infective endocarditis model. We had previously reported that there was a slight growth delay associated with acm allelic replacement (cat) mutant strain TX6051 used in that study. Recently, we generated a nonpolar markerless acm deletion mutant and did not observe a delay in growth. We therefore performed comparative genome sequence analysis of wild-type strain TX82 and TX6051 and found a single mutation, a nonsense mutation in the ccpA gene of TX6051. After correcting this mutation, the growth defect of TX6051 was abolished, implicating a role for CcpA in the growth of E. faecium. To confirm this, we created a ccpA deletion mutant of TX82, which also exhibited a slight delay in growth. Furthermore, the ccpA deletion mutant was attenuated (P = 0.0024) in a mixed-inoculum (TX82 plus TX82 ΔccpA) rat endocarditis model and also in an in vitro competitive growth assay; a ccpA-complemented strain showed neither reduced growth nor reduced virulence. We also found attenuation in the endocarditis model with the new acm deletion mutant although not as great as that previously observed with TX6051 carrying the ccpA mutation. Taken together, our data confirm the role of Acm in the pathogenesis of endocarditis. We also show that CcpA affects the growth of E. faecium, that an intact ccpA gene is important for full virulence, and that a ccpA mutation was partly responsible for the highly attenuated phenotype of TX6051.